Tyranny of the dominant shareholder : Hobson's choice before ONGC Board - Balasubramanian, N., (SAGE knowledge. Cases., 2016)
The case describes a situation where the government as the dominant majority shareholder in a listed Public Sector Enterprise (PSE) directs it through its executive Chairman (a government selected executive) to buy a part of government's stakes in another listed PSE, in which also the government is a majority shareholder.